Case Report: Identification and Functional Analysis of a Homozygous Synonymous Variant in the PLOD1 Gene in a Chinese Neonatal With the Ehlers–Danlos Syndrome - Yan, Xiaodan; Shu, Jianbo; Nie, Yanyan; Zhang, Ying; Wang, Ping; Zhou, Weiwei; Cui, Xiaoyu; Liu, Yang (Frontiers in Pediatrics, 2022)
Background Kyphoscoliotic Ehlers–Danlos syndrome (kEDS; OMIM225400) is a rare autosomal recessive genetic disease caused by variants in the PLOD1 gene. This research was conducted to verify the disease-causing gene in a Chinese neonatal family with the EDS. Methods We recruited a Han Chinese neonate with PLOD1-related kEDS without kyphoscoliosis. Detailed clinical examination and laboratory tests were performed and whole exome sequencing (WES) was used to detect the pathogenic genes of the proband. In vivo experiments (reverse-transcription PCR, quantitative real-time PCR) and in vitro experiments (minigene analysis) were used to verify the function of variants suspected of affecting the splicing process. The effect of the splice site variant on the PLOD1 transcript was analyzed using splice prediction programs NetGene2 and Alternative Splice Site Predictor (ASSP). Results A homozygous synonymous variant c.1095C>T (p.Gly365, rs1032781250) in the PLOD1 gene was found and verified in the family with kEDS. This splicing variant resulted in a premature termination codon of exon 10 and affected the expression of the four bases GCGC. Conclusion Our research showed that the homozygous synonymous variant in PLOD1 was the pathogenic cause in the proband. The combined application of WES and functional studies verified the effect of uncertain gene variants on splicing, upgrading pathogenicity evidence, and determining the cause of disease. This is helpful for the early diagnosis and treatment of kEDS.